2011
DOI: 10.1074/jbc.m111.272302
|View full text |Cite
|
Sign up to set email alerts
|

Human Leucine Zipper Protein sLZIP Induces Migration and Invasion of Cervical Cancer Cells via Expression of Matrix Metalloproteinase-9

Abstract: Background: Proteolytic degradation of the extracellular matrix and basement membranes by matrix metalloproteinases (MMPs) is crucial in tumor invasion and metastasis. Results: sLZIP induces the expression of MMP-9, leading to enhancement of migration and invasion of cervical cancer cells. Conclusion: A novel regulatory mechanism of MMP-9 expression is characterized. Significance: sLZIP is a potential target for preventing the invasion and metastasis of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…They are involved in the degradation of the extracellular matrix (ECM) and play a role in the invasion and metastasis of tumor cells (3,4). Previous studies (36)(37)(38) have suggested that disruption to the ECM during tumor progression is due to an imbalance in the MMP/TIMP ratio. Our study revealed that a significant upregulation of MMP-9 and TIMP-1 protein expression in JEG-3 cells was observed following treatment with TGF-β1 at concentrations of 100 and 200 µg/l.…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in the degradation of the extracellular matrix (ECM) and play a role in the invasion and metastasis of tumor cells (3,4). Previous studies (36)(37)(38) have suggested that disruption to the ECM during tumor progression is due to an imbalance in the MMP/TIMP ratio. Our study revealed that a significant upregulation of MMP-9 and TIMP-1 protein expression in JEG-3 cells was observed following treatment with TGF-β1 at concentrations of 100 and 200 µg/l.…”
Section: Discussionmentioning
confidence: 99%
“…sLZIP negatively regulates transactivation of the glucocorticoid receptor via recruitment of histone deacetylases (HDACs) to the glucocorticoid response element of target genes, leading to suppression of glucocorticoid receptor-mediated gene expression (1). sLZIP is involved in activation of matrix metalloproteinase (MMP)-9 transcription via direct binding to the cAMP-responsive element of the MMP-9 promoter, resulting in an increase in cell migration and invasion in cervical cancer cells (2). sLZIP also promotes phorbol 12-myristate 13-acetate-induced breast cancer cell migration via up-regulation of ADP-ribosylation factor 4 expression (3).…”
mentioning
confidence: 99%
“…The small leucine zipper protein (sLZIP), 2 a novel isoform of human LZIP, is located in the nucleus and functions as a transcription cofactor (1). sLZIP negatively regulates transactivation of the glucocorticoid receptor via recruitment of histone deacetylases (HDACs) to the glucocorticoid response element of target genes, leading to suppression of glucocorticoid receptor-mediated gene expression (1).…”
mentioning
confidence: 99%
“…13,14 Our results showed an association of high LUZP expression with more aggressive tumor behavior, including higher a-FP level, advanced TNM stage, and higher recurrence incidence. High a-FP level and advanced TNM stage are clinicopathologic markers of invasiveness and unfavorable prognosis in patients with HCC.…”
mentioning
confidence: 75%
“…Abnormal expression of LUZP protein is found in many types of tumor such as breast cancer, kidney cancer, cervical cancer, and pancreatic cancer. [11][12][13][14] In this study, we examined expression of LUZP messenger RNA (LUZP mRNA) in tumor versus adjacent noncancerous liver tissues in 77 patients with HCC who received surgical resection. Potential correlations of expression of LUZP mRNA with clinicopathological characteristics of HCC (eg, TNM staging and survival) were also analyzed.…”
Section: Introductionmentioning
confidence: 99%